Greece : Staff Report for the 2001 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2001 Article IV Consultation highlights that strong economic growth continued in Greece in 2001, but the economy was not immune from the global slowdown. GDP increased by about 4 percent, led by robust domestic demand. Investment growth accelerated, following interest rate convergence with euro area rates, and further easing by the European Central Bank, although private consumption was buoyed by rapid credit growth. Core inflation has remained well above the euro area average. Falling energy prices have lowered headline inflation, as in the rest of the euro area.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet